ANALISIS SIFAT FISIKA TANAH LAHAN RAWA PADA PROGRAM KETAHANAN PANGAN POLDA KALSEL - Fachruzi, Ismed (EnviroScienteae, 2026)
Peat swamp land in Landasan Ulin District, Banjarbaru, South Kalimantan, is used by the South Kalimantan Regional Police to implement the current President of the Republic of Indonesia's_National_Food_Security_Program(https://maps.app.goo.gl/TWydCvW2afhQk5BW6?g_st=aw). It is important to understand the characteristics of this soil to determine whether it supports more appropriate management efforts.  For this reason, this research is based on the results of the analysis of the physical properties of the soil: (1) Soil texture is generally classified as Clay Loam Texture, (2) Structure: Crumbly, (3) BD: at 0-20 cm the average is 0.38 g/cc (Very Low in the range of 0.1-0.9 g/cc, this is the nature of peat soil, very porous), (4) PD: 0-20 cm, 0.25-1.67 g/cc (average 0.96 g/cc), and 20-40 cm, 1.84-2.14 g/cc (average 1.99 g/cc), (5) FC (pF 2.54) average 54%, (6) AT (pF 2.54-pF4.2) average 27%., (7) Capillary Pore (pF 2.0) average 54%, (8) Total soil pore/water saturation (pF 1)  average 59%., and (9) Q (permeability) of 0.89 cm/hour (the rate is Moderate according to USDA). Based on the needs of corn plants to grow well, the land studied is Quite Suitable (Class S2) land has light limiting factors, namely very low Bulk and Particle Density.